2016
DOI: 10.1016/j.neuro.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of embryonic exposure to polychlorinated biphenyls (PCBs) on anxiety-related behaviors in larval zebrafish

Abstract: The zebrafish (Danio rerio) is an excellent model system for assessing the effects of toxicant exposure on behavior and neurodevelopment. In the present study, we examined the effects of sub-chronic embryonic exposure to polychlorinated biphenyls (PCBs), a ubiquitous anthropogenic pollutant, on anxiety-related behaviors. We found that exposure to the PCB mixture, Aroclor (A) 1254, from 2 to 26 hours post-fertilization (hpf) induced two statistically significant behavioral defects in larvae at 7 days post-ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 116 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…The study of the consequences of pollutants exposures on behaviour has recently increased, especially for fish, in parallel to the expansion of the use of behaviour as an efficient indicator for neurotoxicity in pharmacology, toxicology, and ecotoxicology. With respect to this, we and others have shown that the exposure of fishes to pollutants using environmentally relevant exposure conditions can induce behavioural disruptions at various developmental stages (e.g., [9,10,11,12,13,14,15,16,17,18]). Other studies have shown that exposure to pollutants could modify monoamine neurotransmitter concentrations (e.g., [19,20,21,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the consequences of pollutants exposures on behaviour has recently increased, especially for fish, in parallel to the expansion of the use of behaviour as an efficient indicator for neurotoxicity in pharmacology, toxicology, and ecotoxicology. With respect to this, we and others have shown that the exposure of fishes to pollutants using environmentally relevant exposure conditions can induce behavioural disruptions at various developmental stages (e.g., [9,10,11,12,13,14,15,16,17,18]). Other studies have shown that exposure to pollutants could modify monoamine neurotransmitter concentrations (e.g., [19,20,21,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…PCB153 induced neostriatal toxicity in adult WKY and SHR rats through changes in the monoaminergic but not amino acidergic neurotransmitter systems 49 . The effect of exposure of zebrafish larvae to a PCB mixture and Aroclor 1254 on neurodevelopment was also observed 50 . Thus, the change in these amino acids in our studies underlined the nerve-endocrine dysfunction in embryos after PCB91/149 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes demonstrated that exposed larvae had enhanced edge preference relative to the control. Furthermore, larvae that were exposed reacted contrarily to a graphical risk comparative to control larvae [ 54 ]. Comprehensive gene expression profiles in cerebellar exhibiting the highest suggestive stimulation of anxiety-like behavior has been warranted via male mice.…”
Section: Influence Of Estrogenic Endocrine Disruptors Exposure On mentioning
confidence: 99%